Phase II study of a combination regimen of gefitinib and pemetrexed as first-line treatment in patients with advanced non-small cell lung cancer harboring a sensitive EGFR mutation. Issue 1 (October 2015) - Yoshimura, Naruo; Kudoh, Shinzoh; Mitsuoka, Shigeki; Yoshimoto, Naoki; Oka, Takako; Nakai, Toshiyuki; Suzumira, Tomohiro; Matusura, Kuniomi; Tochino, Yoshihiro; Asai, Kazuhisa; Kimura, Tatsuo; Kawaguchi, Tomoya; et al.
Graphical abstract: Highlights: We evaluated the combination of gefitinib and pemetrexed in EGFR-mutated NSCLC. The ORR and the median PFS were 84.6% and 18.0 m, respectively. The combination showed a tendency to be more effective in tumors with Del19. The hematological and non-hematological toxicities were mild. This regimen showed a high ORR, long median PFS, and acceptable toxicity. Abstract: Purpose: Patients with advanced non-small cell lung cancer (NSCLC) harboring a sensitive epidermal growth factor receptor (EGFR) mutation have been shown to exhibit a marked response to EGFR-tyrosine kinase inhibitor (TKI) treatment. Pemetrexed and gefitinib were reported to have a schedule-dependent cytotoxic synergism. We evaluated the efficacy and safety of a combination regimen of gefitinib and pemetrexed as first-line chemotherapy in EGFR-mutated NSCLC patients. Patients and methods: Systemic therapy-naïve patients with advanced non-squamous NSCLC harboring a sensitive EGFR mutation were included in this study. Pemetrexed was administered on day 1 at a dose of 500 mg/m 2, and gefitinib was sequentially administered on days 2–16. This treatment regimen was repeated every 3 weeks until disease progression. Results: Twenty-six patients were enrolled in this study. The median number of treatment cycles was 16 (range, 1–35). The overall response rate (ORR) was 84.6% (95% confidence interval [CI], 70.7–98.5%), and the disease control rate (DCR) was 96.2% (95% CI, 88.9–100%). Grade 3/4 hematological toxicities included neutropenia (15.4%), leukopenia (7.7%), and anemia (3.8%). No grade 4 non-hematological toxicities were observed. The main grade 3 non-hematological toxicities were infection (11.5%), increased alanine aminotransferase (11.5%) and aspartate aminotransferase (7.7%) levels, fatigue (3.8%), diarrhea (3.8%), and pneumonitis (3.8%). We observed a median progression-free survival (PFS) of 18.0 months (95% CI, 15.0–21.0 months) and a median survival time (MST) of 32.0 months (95% CI, 28.5–35.5 months). There were no treatment-related deaths. Conclusions: The combination regimen used in this study showed a high ORR, long median PFS, and acceptable toxicity. A future randomized trial on pemetrexed plus gefitinib compared with gefitinib alone is warranted.